2013
DOI: 10.1016/j.resp.2013.07.013
|View full text |Cite
|
Sign up to set email alerts
|

High tidal volume ventilation does not exacerbate acid-induced lung injury in infant rats

Abstract: The impact of high V T -low PEEP in infant rats with preinjured lungs is unknown. After tracheal instillation of saline or acid, two week old rats were ventilated with V T 7 mL/kg and PEEP 5 cmH 2 O or V T 21 mL/kg and PEEP 1 cmH 2 O for 4 h. Airway resistance and the coefficient of tissue elastance, measured via low-frequency forced-oscillation technique, and quasi-static pressure-volume curves deteriorated less with high V T -low PEEP when compared with low V T -high PEEP. IL-6 concentration in bronchoalveol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
1
7
0
Order By: Relevance
“…Moreover, alterations in surfactant PL profile are associated with alveolar instability and impaired lung function. In fact, ARDS patients and ALI animal models showed decreased PC with concomitantly increased SM and lyso-PC levels in BALF (12,18,19,24,39). In our study, both SM and lyso-PC content was significantly higher after V T 24PEEP1 ventilation when compared to all other groups.…”
Section: Discussionsupporting
confidence: 45%
“…Moreover, alterations in surfactant PL profile are associated with alveolar instability and impaired lung function. In fact, ARDS patients and ALI animal models showed decreased PC with concomitantly increased SM and lyso-PC levels in BALF (12,18,19,24,39). In our study, both SM and lyso-PC content was significantly higher after V T 24PEEP1 ventilation when compared to all other groups.…”
Section: Discussionsupporting
confidence: 45%
“…However, many of the experimental studies have used supraphysiologic Vt to study the effects on lung injury, making it difficult to extrapolate the observed differences between pediatric subjects and adults into clinical practice. However, one group of investigators has shown that a Vt in the physiological range exacerbated pre-existing lung injury (80). We therefore propose that VILI is a definite entity in the pediatric population, but that it's propensity increases with increasing age following a yet-unknown function, and reaches susceptibility similar to adults at a yet-unknown age.…”
Section: Clinical Implications and Directions For Future Researchmentioning
confidence: 86%
“…Similar findings were made in mice in a double-hit model in juvenile (21 days) and adult (16 weeks old) C57BL/6 mice treated with aerosolised lipopolysaccharide and ventilated for 3 hours with Vt 15 mL/kg (11). Of note, all experimental studies used supraphysiologic Vt, which challenges translating the results into clinical perspective although one study showed an exacerbation of acid-induced lung injury also occurring when physiological Vt was delivered (12). Furthermore, the findings of these studies may have been influenced by the fact that the injurious stimulus might be lower in the infant rat when Vt was dictated by bodyweight rather than by body size.…”
Section: Vili In Children: Data From Animal Studiesmentioning
confidence: 57%